1998
DOI: 10.1093/carcin/19.11.1913
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive protection against the induction of oxidative DNA damage after hyperbaric oxygen treatment

Abstract: Hyperbaric oxygen (HBO) treatment (i.e. exposure to 100% oxygen at a pressure of 2.5 ATA for a total of three 20 min periods) of human subjects caused clear and reproducible DNA effects in the comet assay with leukocytes. Interestingly, DNA damage was detected only after the first treatment and not after further treatments under the same conditions, indicating an increase in antioxidant defences. We now demonstrate that blood taken 24 h after HBO treatment is well protected against the in vitro induction of DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 35 publications
(34 reference statements)
5
31
0
2
Order By: Relevance
“…These findings are in agreement with the results by other authors who concluded that smoking of less than 20 cigarettes per day had no effect on the change of MN frequency, and that only a few cigarettes per day stimulated protective cell response (Gourabi and Mozdarani 1998;Rothfuss et al 1998). In our study, mothers smoked 5-10 cigarettes per day.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with the results by other authors who concluded that smoking of less than 20 cigarettes per day had no effect on the change of MN frequency, and that only a few cigarettes per day stimulated protective cell response (Gourabi and Mozdarani 1998;Rothfuss et al 1998). In our study, mothers smoked 5-10 cigarettes per day.…”
Section: Discussionsupporting
confidence: 93%
“…We found no difference in DNA repair capacity using any of these tests. These assays were chosen because they are rapid and simple, and they have successfully been employed to screen for radiation-sensitive individuals and individuals with cancer-prone syndromes (Rothfuss et al, 1998;Djuzenova et al, 1999;Kuhne et al, 2004). As a panel, the three tests measure both the immediate effect of radiation on DNA breakage, and DNA repair capacity up to 24 h post-irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors assumed that such result is due to a primary DNA repair mechanism 12 . In a later study, the same group showed that a single HBO session induced adaptive response that protected human blood cells from the genotoxic effects caused by hydrogen peroxide 13 . The great variety of HBO protocols described may confirm differences in presence of MN founded in many studies.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies analyzed HBO mutagenic potential and showed no significant MN increase both in humans 12,13 and animals 14 . However, divergent results were shown in cell cultures 14 and human samples 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation